The Effect of Substituting Rice Bran with Fermented Tofu Pulp in The Basal Diet on Broiler Chicken Performance - David Januarius Djawa Patty; Maria Alfonsa Ngaku; Agnes Yunita Dea; Wilisonius Tena Meo (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
This study aims to determine the effect of substituting rice bran with fermented tofu pulp in the basal diet on the performance of grower phase broiler chickens in Mengeruda Village, Soa District, Ngada Regency. The study used a completely randomized design (CRD) with four treatments and three replicates, namely: P0 (100% basal diet without fermented tofu pulp), P1 (95% basal diet + 5% fermented tofu pulp), P2 (85% basal diet + 15% fermented tofu pulp), and P3 (75% basal diet + 25% fermented tofu pulp), each with three replicates. The population of chickens used in this study was 48, with each treatment consisting of 4 chickens and each treatment consisting of 3 replicates. Thus, 1 treatment required 12 broiler chickens. The research data were statistically analyzed according to RAL (Complete Randomized Design). If there were significant differences, they were followed up with a BNT test. The analysis was performed using SPSS 22.00 software. The parameters observed included feed consumption, weight gain, and feed conversion ratio (FCR). The results showed that the substitution of fermented tofu pulp had a significant effect on broiler chicken performance. Treatment P3 yielded the best results in terms of weight gain and feed conversion efficiency. This improvement in performance was due to better nutrient availability, increased digestibility, and a reduction in anti-nutritional factors.